Gender Differences in Management Style Among Managers in Malaysian Public Organizations - Mohd Rasdi, Roziah (2004)
Traditionally, men and women managers were characterized with different qualities and behaviours. Due to these different qualities, behaviours and gender relations constructs, men and women are said to manage organizations differently. An amount of literature substantiated the above arguments. However, there are also studies indicating that there are no gender differences in management style. Thus, this study primarily aims to answer this argument, i.e. whether there is difference in management style between men and women managers. The respondents of this survey study were 187 managers of whom 124 were men and 63 were women managers, coming from various public organizations in Malaysia. They were sampled randomly from the training participants of Leadership Course series of National Institute of Public Administration (INTAN) for the duration from March 2003 until June 2003. The study adapted and adopted Ministry Style Assessment by Berkley (1995) as the theoretical foundation on the managerial styles exercised by men and women managers. The composite score for the four styles, namely commander, shepherd, maintenance and entrepreneur was identified using the transformed z-scores.Chi-square test for homogeneity showed that gender differences existed in management style. Men managers are most likely to practice commander style of management, followed by maintenance, shepherd and entrepreneur. On the other hand, women managers tend to portray the style of shepherd, entrepreneur, commander and maintenance. The Goodness-of-Fit analysis indicated that the distribution of men managers across the four management styles are more heterogeneous, where majority of them tend to practice commander management style. Though numerically, more women managers showed shepherd management style, the test found that women managers are more homogenous in style, where the distribution of women managers who demonstrate commander, shepherd and entrepreneur management style are almost equal. Results also indicated that there were no differences in the management style of men and women managers based on demographic profile, professional profile and organizational location. The study implies that organizational management should capitalize on the slight variation in management style between men and women to the advantage. Further research is recommended to include psychological factors such as job satisfaction and motivation, and the influence of significant others such as bosses, peers and employees in the analysis.